Properly Cleaning Portable Milking Units: A Step-by-Step Guide: AN392, 4/2024 - Toledo, Izabella; Decubellis, Chris (EDIS, 2024)
This article aims to help small dairy producers learn how to properly clean portable milking machines so they can improve milk quality and prolong the life of milking equipment. This publication is accompanied by one brochure that aims to summarize the steps for proper cleaning of portable milking units. Written by Izabella Toledo and Chris Decubellis, and published by the UF/IFAS Department of Animal Sciences, April 2024.